Recent developments in engineering design for the quasi-axisymmetric stellarator CFQS. (7th December 2021) - Shimizu, A.; Kinoshita, S.; Isobe, M.; Okamura, S.; Ogawa, K.; Nakata, M.; Yoshimura, Y.; Suzuki, C.; Osakabe, M.; Murase, T.; Nakagawa, S.; Tanoue, H.; et al.
Abstract: A quasi-axisymmetric stellarator, the CFQS, has been designed as a joint project of the National Institute for Fusion Science and Southwest Jiaotong University to prove intrinsic advantages of quasi-axisymmetry. Principal parameters of the CFQS are as follows: the major radius is 1 m, the magnetic field strength is 1 T, the aspect ratio is 4, and the toroidal periodic number is 2. The magnetic field configuration is designed based on that of the CHS-qa. Enhanced confinement properties within the context of neoclassical theory are achieved by its quasi-axisymmetric configuration. In the entire radial range, the magnetic well is retained to keep favourable stability features in the magnetohydrodynamic equilibrium. A magnetic field coil system was designed for the CFQS, which consists of 16 modular coils, 12 toroidal field coils, and 4 poloidal field coils. The supporting structure is designed to withstand strong electromagnetic force under 1 T operation, maintaining enough space for heating and diagnostic systems. The mock-up modular coil with the most complicated shape was constructed by Hefei Keye Electro Physical Equipment Manufacturing Co., Ltd. to check manufacturability and the achieved accuracy. A heat-run test was performed to check the temperature rise of conductors, and the capability of 1 T operation was confirmed. After various tests for the mock-up coil, construction of actual modular coils and the vacuum vessel has begun.